Synthesis and Characterization of Optical Properties of Talc/Montmorillonite Nanocomposites via Sol-Gel and Ball Milling Methods - Sefrilita Risqi Adikaning Rani; Eka Cahya Muliawati (Science Journal Get Press, 2025)
Nanocomposites derived from talc (Mg₃Si₄O₁₀(OH)₂) and montmorillonite (MMT) have gained considerable attention due to their tunable optical, mechanical, and thermal properties. This study systematically compares two synthesis techniques—sol-gel processing and ball milling—for fabricating talc/MMT nanocomposites, with a focus on their optical characteristics. The sol-gel method promoted homogeneous nanoparticle dispersion, while ball milling enhanced exfoliation and reduced particle size. Comprehensive characterization via X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), ultraviolet-visible (UV-Vis) spectroscopy, and photoluminescence (PL) spectroscopy revealed that the nanocomposites exhibit strong UV absorption in the 200–400 nm range, a reduced optical bandgap from 4.5 eV to 3.8 eV, and enhanced PL intensity compared to pristine materials. These findings suggest promising applications in UV shielding, optoelectronics, and photocatalytic systems. The study concludes that the choice of synthesis method plays a pivotal role in tailoring the nanocomposites’ structural integrity and optical functionality, with sol-gel favoring intercalation and uniformity, while ball milling enhances exfoliation and defect-mediated performance. This comparative study highlights the critical influence of synthesis method on the structural, morphological, and optical properties of talc/MMT nanocomposites, providing valuable insights for optimizing layered silicate-based materials for advanced functional applications.